Effects of Health Informations System “Dosing Gama” on Time Efficiency in Dosage Adjustment Evaluation - Lilla Prapdhani Agni Hajma; Djoko Wahyono; Fita Rahmawati (Indonesian Journal of Pharmacy, 2020)
Indonesian Ministry of Health shows an increase in patients with impaired kidney and liver function by 10-50% since 2007. The increase is a challenge for pharmacists in conducting pharmaceutical care, which is that dose adjustment for these patients takes a long time. Dosing GAMA, an application that has been developed in 2018, is expected to overcome these obstacles. This study aims to identify the use of the Dosing GAMA application to assist pharmacists in making dose adjustments evaluation more efficient and to assess pharmacist's acceptance of the application. This study was a quasi-experimental study using post-test with control group design. Respondents were recruited by selecting pharmacists according to the inclusion criterion. The control group consisted of 26 pharmacists who made dose adjustments manually, and the intervention group consisted of 26 pharmacists who made dose adjustments using the Dosing GAMA application. Data were obtained by measuring the time required by the pharmacist to make dose adjustments. The intervention group was then asked to complete a perceived acceptance questionnaire. The study indicated that Dosing GAMA could reduce the time needed for dose adjustment evaluation (p<0.05). An average time spent by pharmacists with Dosing GAMA was shorter than that spent by those who made dose adjustments manually without application (13.81±0.78 min vs. 27.5±1.23 min). Overall, the pharmacists have high perceived acceptance of the application. The study results can be used as the basis for developing the application. Furthermore, it is expected that the Dosing GAMA can improve pharmacists’ performance in providing effective pharmaceutical care.